Konsumsi, Status Gizi, Dan Profil Kimiawi-Klinis Mahasiswa UKSW Etnis Dayak Ngaju - Ferry Fredy Karwur; Venti Agustina; Desi Desi; Leviano Leviano (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Background: Nutrition issues in students mostly happen is a life changes phase that affected by lifestyle, so it could affected the behavior that tend to be unhealthy such as smoking, alcohol consumption, hyper-consumption, lack of physical activities and sleepless. This Unhealthy lifestyle potentially caused disease such as metabolic disorders. Therefore this research aim to find out the consumptions, nutritional status and chemical clinical profile and it correlation between nutritional status, anthropometry with chemical/clinical variable in UKSW students with Dayak ngaju ethnic background. This research used cross sectional observational design. Method: The number of respondents were 30 dayak ngaju ethnic students who lived in Salatiga. Data collection techniques using anthropometry measurements, chemical/clinical examination. Food frequency and food recall. Results: The result of anthropometry measurement and metabolic the 30 students showed, underweight 1 respondent (3,3 %), overweight 4 respondent (13,3%) low diastolic pressure (33,3 %), uric acid levels of 30 students is normal (100 %). 3 students with high cholesterol levels (10 %) and 6 students with high momentary glucose levels (20 %). Students nutritional intake using food recall 24 hours showed average energy consumption ±1527.44 kcal, protein ±51.09 gr, Fat ±46.27 gr, carbohydrate ±238.63 gr. Fulfillment of nutrient intake by category adequacy mostly fit in either category, but there were respondents who fall into the category of medium and light the deficit of protein (10%; 0% of respondents), carbohydrate (3.3%; 3.3% of respondents). The Pearson correlation test shows that there is a correlation between cholesterol and supraliaca with a p-value of 0.002 (p≤0.05).